Continuity of Care Midwifery Services for Mrs. P, 24 Years Old, at Mojogedang I Community Health Center, Karanganyar - Kamila, Nudiya Salwa Syifa; Wahidah, Nurul Jannatul; Suharsi, Suharsi; Sukamto, Ika Sumiyarsi (Devotion : Journal of Research and Community Service, 2026)
Maternal and infant mortality rates remain major health challenges in Indonesia, underscoring the need for improved healthcare access and quality. Continuity of Care (CoC) addresses this issue through integrated monitoring from pregnancy to family planning. This qualitative case study applies the CoC approach to provide continuous midwifery care for Mrs. P at Puskesmas Mojogedang I (Mojogedang I Community Health Center). This research aims to explore aspects related to continuous midwifery care for Mrs. P and her baby through midwifery care processes during pregnancy, childbirth, newborn care, postpartum, and family planning. The third-trimester visit results showed that Mrs. P had second-degree obesity. During the delivery process, there was a second-degree perineal rupture, and Mrs. P experienced postpartum hemorrhage due to retained placenta fragments. No complications were found in the newborn. The baby, a female, was born on September 21, 2024, at 2:50 PM WIB, with a birth weight of 3,050 grams and a length of 49 cm. Uterine involution during the postpartum period progressed normally, and the mother chose intrauterine contraceptive use with an IUD (Intrauterine Device). The case assessment from pregnancy to delivery showed a correlation between second-degree obesity and the occurrence of postpartum hemorrhage due to retained placenta fragments. No discrepancies were found between theory and practice.